Particle swarm optimization strategy to increase efficiency of dual active bridge Dc-Dc converter - Suliana, Ab Ghani; Hamdan, Daniyal; Nur Huda, Ramlan; Tiong, Meng Chung (Science & Engineering Research Support Society, 2020)
The isolated bidirectional dual-active bridge (DAB) converter have gained attention in DC-DC applications such as electric vehicle (EV) and energy storage system as the DAB converter provides galvanic isolation and promising high power density. The precise control in controlling the phase angle is important to ensure the optimal efficiency are producing in the DAB system. Thus, this paper proposes an optimization of modulating phase shift angle for DAB system using particles warm optimization (PSO) algorithm. A simulation of 200 kW DAB system has been carried out in MATLAB Simulink to analyse the proposed method under various reference voltage and load changes conditions. Comparative analysis between the proposed method and the PI controller performance is presented. As expected, the DAB system with proposed method produces fast convergence speed and higher power efficiency as compared to the DAB system with PI controller